Zajal al-Asīr fī Madḥ al-Shaykh Usman Al-Bashir, Qaṣīdah Nūnīyah li-Musa Kalim Al-Qali: Dirāsah Taḥlīlīyah Adabīyah - Saleh Muhammad Kabir; Zakir Alhaj Shariff; Muhammad Tukur Abdullahi (Al-Ma‘rifah, 2021)
This study aims to study the life of the poet Musa Kalim Al-Qali and his eulogy poem. The method used in this study is the descriptive-analytical approach, where the researchers read the selected poem and then follow it with study and analysis. The poem chosen was Zajal al-Asīr which contains his praise to Sheikh Usman Al-Bashir. The results of this study indicate that (1) the beginning of the poem (maṭla‘ al-qaṣīdah) invites the reader to follow what he will say about the praised Sheikh; (2) good disposal (ḥusn al-takhalluṣ) of the poem, the poet proceeded directly with the topic, noting that he did not explore his poem with a prologue or propaganda introduction; (3) a good syllable (ḥusn al-maqṭa‘) in the poem, the last words upon which the poet stood was well tolerated and kept a pleasure in listening in the most eloquent expression and the most beautiful meaning; (4) the sincerity of emotion (ṣidq al-‘āṭifah), the poem was distinguished by the sincerity of emotion, the heat of feeling, and the acuity of feeling.